"Family and work in rural socities, perspectives on non-wage labour / edited by Norman Long" (London, 1984)
This book covers the following topics Aspects of non-capitalist social relations in rural Egypt: the small peasant household in an egyptian Delta Village; Cash crop production and family labour: Tobacco growers in corrients, Argentina; Interhousehold co-operation in Perus southern Andes: a case of mulktiplique sibling-group marriage; Co-operation on and between eastern finnish family farms. The estimation of work in a northern finnish farming community; A note on the custom of playing off on family farms in Poland; Womens work in rural south-westh england. Domestic work in rural iceland:An historical overview; The organization of labour in an Israeli Kibbutz.
Keywords: Agricultural Wages